The Role of Local Government in Fostering the Economic of Community: - Kencana, Eka N (E-Journal of Tourism; Volume 6 Number 1 (March 2019)DO - 10.24922/eot.v6i1.47283, 2019)
For Bali and its administrative territories, tourism and the related sectors are very important for their development agendas. Referring to Bali Statistic Office, the agricultural sector and food and beverages services, contribute more than one-third of Bali’s gross regional domestic product (PDRB) for the year 2017. It is not surprising, then, tourism and the related industries have been positioned as the important pillars for the economic development of Bali. Consisting of nine regencies or city, Klungkung, after Denpasar city as the capital of Bali, is the second smallest region with its area is 315 km square or approximately 5.59 percent of Bali area as much as 5,366.66 km square. In the last five years, the local government of Klungkung is intensively developing Nusa Penida district as a marine tourists destination. The aim of this essay is to study the causal relationship between government roles and the economic benefit of tourism for the local people. A hundred and thirteen people of Nusa Penida were questioning their perception regarding the benefits of tourism for their families. Applying variance-based SEM, this work found the roles did not directly affect the economy of local people. However, by the mediation of tourists' behavior as well as the tourism industries at Nusa Penida, the role of Klungkung’s government is significantly influence the economy of Nusa Penida people.